Developing a tool for evaluation of causes of futile care in intensive care units - Leili Yekefallah; Tahereh Ashktorab; Houman Manoochehri; Hamid Alavi Majd (Wolters Kluwer Medknow Publications, 2019)
Background: In Iran, futile care has become a challenge for intensive care nurses. The aim of the study was to develop a tool for assessing the reasons of futile care at intensive care units (ICUs). Materials and Methods: A sequential mixed method in three stages was applied. In the first stage, a phenomenological study was performed with van Manen's method by interviewing 25 nurses at ICUs of 11 hospitals in Qazvin. To extract the items of the tool in the second stage, the concept of futile care in ICUs and its reasons were defined. Ultimately, the psychometric properties of the questionnaire were evaluated with face validity, content validity (quantitative and qualitative), construct validity (exploratory factor analysis), internal consistency (Cronbach's alpha), and test-retest reliability. Results: The initial tool had 119 questions. After validation, 39 items remained in the final questionnaire. Five extracted factors were as follows: professional competence (14 items), organizational policy (9 items), socio-cultural factors (7 items), personal beliefs and values (4 items), and legal issues (5 items). Cronbach's alpha for the whole questionnaire was 0.91 (range: 0.71-0.96). The test-retest reliability was 0.87 (p < 0.001). Conclusions: Nursing managers and clinical nurses can use this tool to identify the causes of futile care and reduce it in their clinical settings. Policy makers can use this tool for improving the management of ICUs.